Two Fully Automated Web-Based Interventions for Risky Alcohol Use: Randomized Controlled Trial - Tensil, Marc-Dennan; Jonas, Benjamin; Strüber, Evelin (JMIR Publications, 2013)
BackgroundExcessive alcohol use is a widespread problem in many countries, especially among young people. To reach more people engaging in high-risk drinking behaviors, a number of online programs have been developed in recent years. Change Your Drinking is a German, diary-based, fully automated alcohol intervention. In 2010, a revised version of the program was developed. It is more strongly oriented to concepts of relapse prevention than the previous version, includes more feedback, and offers more possibilities to interact with the program. Moreover, the program duration was extended from 10 to 14 days. ObjectiveThis paper examines whether the revised version of Change Your Drinking is more effective in reducing alcohol consumption than the original version. MethodsThe effectiveness of both program versions was compared in a Web-based, open, randomized controlled trial with follow-up surveys 6 weeks and 3 months after registration. Participants were recruited online and were randomly assigned to either the original or the revised version of Change Your Drinking. The following self-assessed outcomes were used: alcohol use days, alcohol intake in grams, the occurrence of binge drinking and risky drinking (all referring to the past 7 days prior to each survey), and the number of alcohol-related problems. ResultsA total of 595 participants were included in the trial. Follow-up rates were 58.0% after 6 weeks and 49.6% after 3 months. No significant group differences were found in any of the outcomes. However, the revised version was used by more participants (80.7%) than the original version (55.7%). A significant time effect was detected in all outcomes (alcohol use days: P=.002; alcohol intake in grams: P<.001; binge drinking: P<.001; alcohol-related problems: P=.004; risky drinking: P<.001). ConclusionsThe duration and complexity of the program played a minor role in reducing alcohol consumption. However, differences in program usage between the versions suggest the revised version was more attractive to participants. Trial RegistrationInternational Standard Randomized Controlled Trial Number (ISRCTN): 31586428; http://www.controlled-trials.com/ISRCTN31586428/ (Archived by WebCite at http://www.webcitation.org/6BFxApCUT)